SEXUAL MINORITIES NARRATIVES IN INDIAN WEB SERIES: THE QUEER VISIBILITY AND BEYOND - Sikdar, Ananya; K. Karthik (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Web series across the globe have emerged as a significant medium for sharing diverse content and have evolved into an alternative space for sexual minorities. In India and across the globe, web series are becoming increasingly popular, particularly among youth. Historically, Indian media has stereotyped the image of transgender and homosexual people in various ways by depicting them as helpless, submissive, and victims. Today, web series in India are emerging as a space for queer representation and continue to serve as an inclusive space for queer content. In this context, it is essential to study how such web series portray the struggles, trauma, and identity issues of sexual minorities in India. Hence, this study attempts to investigate the representation and portrayal of sexual minorities, their problems, and their fight for rights in Indian web series. Using qualitative content analysis, this study analyses the four web series that were released from 2017 to 2023 with the following objectives: to identify how the web series addresses the social issues related to sexual minorities; to explore the portrayal of sexual minority characters in web series; to examine the narratives on the stereotypes, trauma, and taboos of the sexual minorities portrayed in web series.